The Phronesis of the Stoic Sage - Lories, Danielle (1999)
The traditional image of the stoic sage, retired and solitary, indifferent to all that does not "rely" on him, and thus to the most part of events that mark the course of the world and of human lives, is a simplistic view that ought to be reconsidered. To do so, we try to show that the virtue borrowed from the sophos by the texts of ancient stoicism has indeed the traits of the Aristotelian phronesis, political excellence and thus virtue of human relations. The A. conducts this approach by examining the sources that render stoic phronesis as one of the tirst virtues, then as the tirst of the tirst virtues, and then through virtue's relationships in its unity with a variety of virtues.